The relationship between retaining talent and job satisfaction in selected public higher education - Lukman@Zawawi, Mohamad; Kamal, M.Y.; Zam Azima, Zamri (2017)
Retain a best talent has become a main agenda in any organizations especially in higher education sector. This sector has become very competitive in serving a very good education to the society. In having a best talent with the skills and expertise, it will help the institution to achieve their mission and vision. Thus, one way of retain the best employee of the organization; top management needs to know theoretically and mathematically about their employee job satisfaction (JS). Once their employee satisfied with the job and environment, surely they will retain longer in the institutions. Thus, this research is about to examine the relationship between retaining talent with JS in selected public higher education in Malaysia. Quantitative approach has been used in order to collect primary data from 238 respondents in selected public universities which are Universiti Sains Malaysia (USM), Universiti Pendidikan Sultan Idris (UPSI) and Universiti Teknologi Mara (UiTM). Information obtained from this method has been analyzed using IBM Statistical Package Social Sciences (SPSS). As a result, there was a moderate relationship recorded between retaining talent and JS. However, USM scored slightly higher correlation between retaining talent and JS as compared to other two public higher educations. In conclusion, employees will retain longer when they are fully satisfied with their job, environment as well as their salary. Thus, it is quite important to the public higher education to take an effective approach to cater their employees need and wants in order to retain their best employees which directly help the public higher education to success.